Enhancing Soil Physicochemical Properties and Fruit Production of Rosa roxburghii With Biochar‐Based Fertilizer in Karst Agricultural Systems - Xiang, Yangzhou; Luo, Jun; Liu, Ying; Luo, Yang; Bolan, Nanthi; Fan, Jing; Shurpali, Narasinha J.; Bhattarai, Hem Raj; Siddique, Kadambot H. M.; Li, Yuan (Wiley-Blackwell, 2025)
The development of sustainable agricultural practices in Karst regions faces significant challenges due to inherent soil limitations and complex terrain characteristics. This study investigated the effects of biochar-based fertilizers on soil properties and fruit quality of chestnut rose (Rosa roxburghii) in Southwest China's Karst region. Three biochar types derived from R. roxburghii pomace (RPB), discarded mushroom substrate (DMB), and chili straw (CSB) were evaluated at five application rates in combination with conventional fertilizers (with nitrogen, phosphorus, and potassium). Results revealed that the RPB4 treatment (70% biochar) significantly enhanced soil moisture content (61.37%), organic matter content (22.73%), and available nitrogen (22.74%) compared to controls. Fruit quality parameters showed significant improvements under optimal biochar treatments, with vitamin C content increasing by 67.94% (DMB4), total flavonoids by 120.06% (RPB4), and soluble sugars by 148.69% (RPB4). Structural equation modeling revealed significant direct effects of biochar application on soil water content (Standardized path coefficient = 0.60) and pH (0.80). Principal component analysis identified RPB4 as the optimal treatment combination, explaining 69.328% of total variance in soil and fruit properties. These findings provide quantitative evidence for the efficacy of biochar-based fertilizers in improving both soil quality and fruit characteristics in Karst agricultural systems, while establishing optimal application rates for sustainable orchard management.
Keywords: biochar-based fertilizer; fruit quality; karst agriculture; Rosa roxburghii; soil amelioration; sustainable soil management